Review of the Translation of the Book of Criminal Law in European Council - Alireza Taghipour (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
International law has so far made remarkable progress in two areas. One of these is human rights and the other is the international criminal law. After World War II, numerous international and regional documents were adopted in the field of human rights. The European convention for the protection of human rights and fundamental freedoms is the first regional instrument which provides a judicial institution, the European court for the protection of human rights, as a monitoring mechanism on execution of the convention’s provisions. In the field of international criminal law, the focus has been on prosecuting and trial of individuals who violate humanitarian laws, and international criminal tribunals have been prosecuting perpetrators of these catastrophes. The book of Criminal Law in European Council, which has been translated comprehensively, expresses the translator's expertise in both areas. But this specialization required that the pages, however briefly, were allocated to the other European court decisions to make the terms of the convention clearer as well as to the judgments of the international criminal tribunals which provided interpretations that were contrary to the interpretations of the European court in some human rights in order to comprehensively cover the issue and its relevance to the goals and educational needs of graduate students.